2021
DOI: 10.1515/jpem-2021-0067
|View full text |Cite
|
Sign up to set email alerts
|

Invisible burden of COVID-19: enzyme replacement therapy disruptions

Abstract: Objectives Lysosomal storage diseases (LSD) constitute an important group of metabolic diseases, consisting of approximately 60 disorders. In some types of lysosomal diseases, enzyme replacement therapy (ERT) is administered intravenously in weekly or biweekly doses. Unfortunately, scheduled ERT during COVID-19 was disrupted. We considered the possibility of adverse outcomes caused by the disruption in the treatment of patients with lysosomal storage disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 20 publications
5
26
0
Order By: Relevance
“…As might be expected and in line with recent reports [ 3 , [5] , [6] , [7] , [8] , [9] , 11 ], HCPs noted that there had been some interruptions to treatment because of the COVID-19 pandemic; 38.0%, 32.6%, and 15.2% of respondents noted that <1%, 1–10%, or > 10–20% of patients, respectively, had missed infusions. A small proportion of HCPs reported that patients had missed >20–50% or > 50% of infusions (4.3% and 5.4% of respondents, respectively).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…As might be expected and in line with recent reports [ 3 , [5] , [6] , [7] , [8] , [9] , 11 ], HCPs noted that there had been some interruptions to treatment because of the COVID-19 pandemic; 38.0%, 32.6%, and 15.2% of respondents noted that <1%, 1–10%, or > 10–20% of patients, respectively, had missed infusions. A small proportion of HCPs reported that patients had missed >20–50% or > 50% of infusions (4.3% and 5.4% of respondents, respectively).…”
Section: Resultssupporting
confidence: 86%
“…Other factors noted by respondents as free text entries included psychiatric effects, stress and fear, access to vaccination, continued treatment, optimum care, disease surveillance and disease management, and access to school, social, and community services. The concerns noted by HCPs for their patients in this survey appear to align with the results of published patient surveys [ [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. Furthermore, most respondents were concerned that the risks associated with contracting COVID-19 for patients with LSDs may be higher than for the general population; 47.8% of respondents were ‘somewhat concerned’ and 34.8% of respondents were ‘greatly concerned’; however, 17.4% of respondents were ‘not concerned’ that risks may be higher in this patient population.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…agalsidase beta and agalsidase alfa for Fabry disease; imiglucerase and velaglucerase alfa for Gaucher disease; alglucosidase alfa for Pompe disease) intravenous infusions. Disruptions in treatment, either intentional or forced by unavoidable events, can potentially lead to a deterioration of clinical parameters and quality of life and could lead to potential adverse outcomes, such as cardiac events and/or decline of renal function in Fabry patients, visceromegaly and bone crisis in Gaucher patients, worsening of respiratory function and walking capacity in Pompe and MPS patients 27–31 …”
Section: Resultsmentioning
confidence: 99%